2009
DOI: 10.1007/s10439-009-9855-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Reduced Conduction Reserve in the Diabetic Rat Heart: Response to Uncoupling and Reduced Excitability

Abstract: Experimental results have shown that action potential (AP) conduction in ventricular tissue from streptozotocin-diabetic (STZ) rats is compromised. This was manifest as increased sensitivity of conduction velocity (CV) to the gap junction uncoupler heptanol, as well as increased sensitivity of CV to reduced cellular excitability due to elevated extracellular K(+) concentration, in the STZ hearts. This "reduced conduction reserve" has been suggested to be due to lateralization of connexin43 (Cx43) proteins, ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
(77 reference statements)
3
9
0
Order By: Relevance
“…It was also shown that the Cx43 was lateralized in diabetic rat hearts [17]. Further, using computer simulations, these investigators predicted that changes in I Na properties could possibly explain their experimental findings [36]. Indeed, our experiments and simulations confirm an important role for I Na in the impaired propagation in diabetes.…”
Section: Discussionsupporting
confidence: 68%
“…It was also shown that the Cx43 was lateralized in diabetic rat hearts [17]. Further, using computer simulations, these investigators predicted that changes in I Na properties could possibly explain their experimental findings [36]. Indeed, our experiments and simulations confirm an important role for I Na in the impaired propagation in diabetes.…”
Section: Discussionsupporting
confidence: 68%
“…However, effects of increased cell size and GJ distribution in hypertrophied hearts are difficult to study experimentally. It is known that cell size can have a strong effect on impulse propagation (12)(13)(14)(15). In a study by Spach et al (13), an increase in cell size resulted in higher conduction velocity (q),in accordance with findings of Ghali et al (15), who showed that decreased cell size can negatively affect q.…”
Section: Introductionsupporting
confidence: 65%
“…It is known that cell size can have a strong effect on impulse propagation (12)(13)(14)(15). In a study by Spach et al (13), an increase in cell size resulted in higher conduction velocity (q),in accordance with findings of Ghali et al (15), who showed that decreased cell size can negatively affect q. In contrast, McIntyre et al (16) found a negative correlation between cell diameter and q in human ventricular tissue, which seems paradoxical, because an increase in cell diameter reduces the intracellular resistance.…”
Section: Introductionmentioning
confidence: 99%
“…2 demonstrate that the conduction slowing observed in acute ischemia is more pronounced in hearts from STZ-induced diabetic rats than in hearts from healthy controls. This is to be expected, given our previous observations that STZ-induced diabetic hearts suffer from a reduced conduction reserve that is related to the lateralization of Cx43 proteins (18,40,45). Acute ischemia can affect cardiac CV through at least two mechanisms: reduced excitability and reduced coupling.…”
Section: Conduction Slowing During Acute Ischemia In Stz-induced Diabmentioning
confidence: 73%